MINERAL CONTENT PROFILE OF CARAPACE FLOUR, CHITIN, AND CHITOSAN SLIPPER LOBSTER (Thenus orientalis) - Putra, Harifa Syah; Hasan, Bustari; Karnila, Rahman; Ghazali, Tengku Muhammad (Asian Journal of Aquatic Sciences, 2024)
Slipper lobster live on the bottom of sandy and muddy waters at a depth of 10-200 m and are found throughout Indonesian waters. The carapace is the most significant part of its body, of which approximately 50% is a source of waste, but it can be utilized as functional food in the form of chitin and chitosan. One of the determinations of chitin and chitosan quality depends on the demineralization process. The potential of this shrimp has not been fully utilized due to the lack of information on mineral content after the demineralization process. This study aims to obtain information on flour, chitin, and chitosan mineral content. This research used a descriptive method. The parameters observed were yield, water, ash, and mineral content (K, Mg, Ca, Na, Fe, and P). The results showed that slipper lobster weighed about 80-240 g with a length of 15-25 cm with the yield and mineral content of flour, chitin and chitosan of slipper lobster carapace as follows: yield 29.04%, 41.02%, 33.42%, water 2.36%, 3.96%, 3.25%, ash 52.89%, 8.27%, 3.16%, potassium 55.73 mg/L, 9.09 mg/L, 4.55 mg/L, magnesium 37.23 mg/L, 5.59 mg/L, 5.95 mg/L, calcium 766.87 mg/L, 137.62 mg/L, 126.91 mg/L, sodium 146.62 mg/L, 17.82 mg/L, 10.73 mg/L, iron 12.82 mg/L, 1.89 mg/L, 1.72 mg/L, phosphorus 0.17 mg/L, 0.06 mg/L, 0.05 mg/L.